2018
DOI: 10.1108/maj-02-2017-1518
|View full text |Cite
|
Sign up to set email alerts
|

An empirical examination of the determinants of audit report delay in France

Abstract: Purpose This study aims to investigate the determinants of delay in publishing audited reports. Design/methodology/approach The research is conducted on a sample of French listed companies, covering the period of five years (from 2010 to 2014). The authors use pooled ordinary least squares regression analysis, modeling audit delay as a function of the following explanatory variables relating to the attributes of companies and their auditors. Findings A statistically significant association is found between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
0
36

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 33 publications
10
43
0
36
Order By: Relevance
“…Thus, audited companies by an international auditing firm "BIG4" are the first who have a tendency to disclose their environmental information which is in the CSR reports to different users. This finding is consistent with the findings of Daoud et al (2014); Fauzi and Locke (2012); Khoufi and Khoufi (2018) noted that due to greater resources owned by large firms such as adequate qualified staff can reduce the time taken to complete the audit work. So, our third hypothesis H3 is thus confirmed.…”
Section: Regression Analysis and Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Thus, audited companies by an international auditing firm "BIG4" are the first who have a tendency to disclose their environmental information which is in the CSR reports to different users. This finding is consistent with the findings of Daoud et al (2014); Fauzi and Locke (2012); Khoufi and Khoufi (2018) noted that due to greater resources owned by large firms such as adequate qualified staff can reduce the time taken to complete the audit work. So, our third hypothesis H3 is thus confirmed.…”
Section: Regression Analysis and Discussionsupporting
confidence: 89%
“…Cormier and Magnan (1999), Cormier and Magnan (2003) and Aerts et al (2008) in their studies based on a sample of Canadian firms, found a negative relationship between debt level and environmental disclosure. Moreover, financial debt has been studied empirically by some researchers to assess whether it bears any relationship to timeliness disclosure (Al-Ajmi, 2008;Khasharmeh and Aljifri, 2010;Khoufi and Khoufi, 2018). Khasharmeh and Aljifri (2010) and Al-Ajmi (2008) showed that the level of debt is an influential factor on timely disclosure and concluded that timely disclosure determines the quality of disclosure.…”
Section: The Size Of the Companymentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, any future studies using data from the post‐December 15, 2010, period need to take this new auditing standard into account in their research design. However, evidence about ARL that uses data exclusively after the adoption of the revised international standard suggests that there are no changes in the audit report lag model determinants (Khoufi and Khoufi, 2018). Given the changes to the standard, we call for research on the ARL model that incorporates post the implementation of this new international reporting date convention evidence on ARL determinants.…”
Section: Conclusion and Discussionmentioning
confidence: 99%